Draft genome sequence of strain HIMB100, a cultured representative of the SAR116 clade of marine Alphaproteobacteria. Issue 3 (November 2011) - Grote, Jana; Bayindirli, Cansu; Bergauer, Kristin; Carpintero de Moraes, Paula; Chen, Huan; D'Ambrosio, Lindsay; Edwards, Bethanie; Fernández-Gómez, Beatriz; Hamisi, Mariam; Logares, Ramiro; Nguyen, Dan; Rii, Yoshimi; et al.
Abstract Strain HIMB100 is a planktonic marine bacterium in the classAlphaproteobacteria . This strain is of interest because it is one of the first known isolates from a globally ubiquitous clade of marine bacteria known as SAR116 within the familyRhodospirillaceae . Here we describe preliminary features of the organism, together with the draft genome sequence and annotation. This is the second genome sequence of a member of the SAR116 clade. The 2, 458, 945 bp genome contains 2, 334 protein-coding and 42 RNA genes.